Understanding and building clean(er) sport together: Community-based participatory research with elite athletes and anti-doping organisations from five European countries - Petróczi, A.; Heyes, A.; Thrower, S. N.; Martinelli, L. A.; Backhouse, S. H.; Boardley, I. D. (Psychology of Sport and Exercise, 2021)
Background: In sport the narrative is changing from anti-doping to pro-clean sport. Yet, our understanding of what `clean sport` means to athletes is notably absent from the literature. Objectives: Working together with elite athletes and National Anti-Doping Organisations (NADOs), this study explored the meaning and importance of `clean sport` and `clean athlete identity`. Design: Community-based participatory research design was employed to explore (a) how elite athletes define clean sport and being a clean athlete; (b) the hopes and challenges associated with clean sport and being a clean athlete; and (c) what can be done in anti-doping to elicit clean sport. Methods: Five elite athletes in five European countries (Germany, Ireland, Netherlands, Slovenia and United Kingdom) were recruited as co-researchers by their respective NADOs, trained for their role as co-researchers and individually interviewed. Seventy-seven elite athletes were then purposefully recruited for 12 athlete-led national focus groups. Finally, the five athlete co-researchers and five athlete participants took part in one 2.5-h long international focus group. Results: Reflexive thematic analysis resulted in generating four overarching themes: `clean is being true to the self`, `clean performance enhancement has multiple meanings`, `clean is not a solo act` and `the problems and solutions are systemic`. Collectively, the themes showed that the clean athlete identity is generally rooted in upbringing, early experiences and love of sport; and characterised by continued, intrinsically motivated commitment to fundamental values and morals acquired in childhood. In contrast, the concept of clean performance-enhancement is highly idiosyncratic and flexible. Elite athletes value anti-doping efforts but their experiences of disparity and unfairness in doping control undermine their trust in anti-doping. Conclusion: Clean athlete identity is a social endeavour and artefact, which needs to be reflected in and developed through evidence-informed anti-doping interventions. Raising athletes' voices via collaboration and participatory research can be an enriching experience for athletes and researchers alike, and a worthwhile endeavour for sport organisations with responsibility for anti-doping. To make anti-doping education personally relevant, the richness of individual interpretation of `clean` for the self (i.e., clean athlete identity) and performance-enhancement must be acknowledged, respected and cultivated.